Analisa Rugi-Rugi Pelepasan Energi Sistem Penyimpanan Energi Potensial Gravitasi Jenis Menara Beban - rizki pratama putra (KILAT, 2020)
This study discusses the mechanical losses of a gravitational potential energy storage system of load tower types. The aim of this research is to investigate the characteristics of mechanical losses with varied mechanical torque. Analysis of the friction friction theory of bearings and pulleys using the Harris model, then the prototype of the energy storage system is tested directly with the weight load varying in weight to see the characteristics of mechanical losses that occur in prototypes. This information will later be taken into consideration to design and optimize the energy storage system in terms of the selection of falling loads and how to design the energy charging and discharging mechanism. The results obtained are torque losses measurement are partly proportional to the falling mass applied to the system. The value of losses does not increase linearly with the addition of the mass of the falling load. This provides information in considering optimum falling mass weight for energy charging process and also how to consider the control mechanism of energy storage